Telemonitoring for COVID-19 positive pregnant women; feasibility and user experience of SAFE@home Corona: prospective pilot study - Shinta L. Moes; Martine Depmann; Titia A. Lely; Mireille N. Bekker (BMC, 2022)
Abstract Background COVID-19 has catalysed digital innovations enabling remote healthcare. Pregnant women are at increased risk for severe course of COVID-19 infection. Also, the pandemic has a negative emotional impact on pregnant women as they worry about their own health and the health of their unborn child. We developed a telemonitoring platform called SAFE@home-corona consisting of a pulse oximeter and an app with symptom checklist. The aim of this study was to examine the feasibility, defined by compliance to the platform and by monitoring the course of COVID-19, patient satisfaction and user experience of a telemonitoring platform in COVID-19 positive pregnant women in the Netherlands. Methods We conducted a prospective pilot study among Dutch-speaking COVID-19 symptomatic pregnant women. Women were asked to monitor their oxygen-saturation with a pulse oximeter and COVID-related complaints with an in-app questionnaire daily. Oxygen-saturation and complaints were monitored by the Medical Management Centre with triage protocol. COVID-19, pregnancy, and user experience data were collected. To assess feasibility, compliance of daily self-monitoring and compliance of all intended measurements were calculated. Severity of COVID-19 was assessed via the platform and medical record. Patient satisfaction and user experience were measured through a self-developed questionnaire. Results Twenty-eight women were eligible of which 27 (93.1%) completed the study. Compliance of daily measurement and all intended measurements was high with 98.9 and 93.9%, respectively. Six women were hospitalized, of whom one to the intensive care unit. Overall, women indicated high satisfaction scores, varying from 8 to 10/10. Women were more concerned for the health of their unborn child or family then for themselves (66.7%). They stated that the platform offered reassurance. Patients would highly recommend the platform to pregnant peers during COVID infection. Conclusions This pilot study demonstrated feasibility of the SAFE@home-corona platform for self-monitoring COVID-19 course in pregnant women. Patients were satisfied, it offered reassurance, women would recommend use to peers. Upscaling the platform is needed to draw conclusions from the early signalling abilities and to keep evaluating patient satisfaction. The platform has great potential for self-monitoring of COVID-19 and possibly other pulmonary infections in pregnant women.